With Feeling: How Emotions Shape Negotiation. Issue 4 (October 2014) - Olekalns, Mara; Druckman, Daniel
<x xml:space="preserve">Abstract</x> Recognition of the role played by emotions in negotiation is growing. This article synthesizes current research around four broad themes: moves and exchanges, information processing, social interaction, and context. The authors' review reveals that much of the research on this topic has focused on two key emotions, anger and happiness. More recently, negotiators have turned to other emotions such as guilt and disappointment, demonstrating that not all negative emotions have the same consequences, or activate the same regions of the brain. Focusing on social interaction, the authors note that negotiators may influence each others' emotions: whether negotiators converge to anger or happiness has different consequences for agreement. Researchers have broadened their examination of emotion by considering how external factors such as power, the number of negotiators, culture, and gender influence the impact of emotional expression. The authors also consider the function and impact of expressing authentic emotions, or choosing to use emotions strategically to gain an advantage — an issue that raises important ethical questions for negotiators. The article concludes with some practical implications of the research.